2020
DOI: 10.3390/jmmp4030080
|View full text |Cite
|
Sign up to set email alerts
|

Minimisation of Heating Time for Full Hardening in Hot Stamping Using Direct Resistance Heating

Abstract: To obtain enough hardness of the die-quenched products after hot stamping using direct resistance heating, the effects of the electrifying condition and initial microstructure of the quenchable steel sheet on hardness were examined in a hot bending experiment. The steel sheet was heated up to 900 °C in 3 to 10 s. The required heating time was shortened by normalising heat treatment due to the fine grain size of the sheet. The standard deviation of the hardness of the sheet heated to 900 °C in 3.2 s without tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The microstructure of the as-received tube consists of the striped area of pearlite, dark area of ferrite, and small precipitates of cementite. The results revealed that the steel tube was heated above the austenitizing temperature, and then was rapidly cooled by contacting with dies during bulging to ensure a martensitic transformation, even for the comparatively short heating time of resistance heating [27]. The microstructures at the center of the formed tubes were analyzed by scanning electron microscopy (SEM; JSM-5510, JEOL Ltd., Tokyo, Japan) as shown in Figure 22.…”
Section: Influence Of Sealed-air Hot Tube Gas Forming On Hardness Dis...mentioning
confidence: 99%
“…The microstructure of the as-received tube consists of the striped area of pearlite, dark area of ferrite, and small precipitates of cementite. The results revealed that the steel tube was heated above the austenitizing temperature, and then was rapidly cooled by contacting with dies during bulging to ensure a martensitic transformation, even for the comparatively short heating time of resistance heating [27]. The microstructures at the center of the formed tubes were analyzed by scanning electron microscopy (SEM; JSM-5510, JEOL Ltd., Tokyo, Japan) as shown in Figure 22.…”
Section: Influence Of Sealed-air Hot Tube Gas Forming On Hardness Dis...mentioning
confidence: 99%
“…The causes of the occurrence of forging defects can also be other aspects, e.g., improper temperature of the charge material, the use of too strong drafts, badly made tools, imprecise removal of scale or underdeveloped technology. Most of the reasons for defect formation are related to the activities of the production plant, but sometimes there are also discrepancies independent of the forge, whereby die forges have the possibility to control and supervise such defects/problems in order to prevent a reduction in product quality [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of high strength steel sheets is generally employed to balance the high strength and weight reduction of the body-in-white, the application of hot stamping increases [1]. In hot stamping, quenchable steel sheets or tubes are transformed into austenite by heating to about 900 • C and then into martensite by die quenching [2,3]. The high strength of the hot-stamped parts is attained by the heat treatment.…”
Section: Introductionmentioning
confidence: 99%